2012
DOI: 10.1159/000340038
|View full text |Cite
|
Sign up to set email alerts
|

Overweight is Associated with Airflow Obstruction and Poor Disease Control but Not with Exhaled Nitric Oxide Change in an Asthmatic Population

Abstract: Background: The role of an elevated body mass index (BMI) in asthma remains controversial. Objectives: To investigate the relationship between overweight (BMI >25 and ≤30), lung function, disease control, and airway inflammation in an asthmatic population. Methods: We consecutively studied 348 patients (age 43 ± 16 years; 211 females). In all patients, BMI, spirometry, the Asthma Control Test (ACT), and fractional exhaled nitric oxide (FeNO; ppb) were measured. Results: One hundred forty-five patients were ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…To reinforce this message, we also found that the ACQ score and the number of asthma exacerbation episodes during the last year are significantly higher in obese severe asthmatics in comparison to the other two studied groups, leading to the concept that the severe asthmatic patient with lower BMI is better “controlled” and has a lower frequency of exacerbations in comparison with the severe asthmatic patient with higher BMI. These results are in agreement with previous studies showing that overweight patients with asthma had worse disease control as compared with normal weight patients [25] and that obesity was associated with poorer asthma control as expressed by recurrent episodes of exercise-related respiratory symptoms [26]. In addition, in our study we found that the dose of corticosteroids required during the last year and LABA treatments are significantly higher in the group of severe obese asthmatic patients, strongly supporting the concept of the refractoriness to corticosteroids in severe asthma.…”
Section: Discussionsupporting
confidence: 94%
“…To reinforce this message, we also found that the ACQ score and the number of asthma exacerbation episodes during the last year are significantly higher in obese severe asthmatics in comparison to the other two studied groups, leading to the concept that the severe asthmatic patient with lower BMI is better “controlled” and has a lower frequency of exacerbations in comparison with the severe asthmatic patient with higher BMI. These results are in agreement with previous studies showing that overweight patients with asthma had worse disease control as compared with normal weight patients [25] and that obesity was associated with poorer asthma control as expressed by recurrent episodes of exercise-related respiratory symptoms [26]. In addition, in our study we found that the dose of corticosteroids required during the last year and LABA treatments are significantly higher in the group of severe obese asthmatic patients, strongly supporting the concept of the refractoriness to corticosteroids in severe asthma.…”
Section: Discussionsupporting
confidence: 94%
“…Two of them reported results for persons with asthma, with one finding no association [14] and the other a negative association [15]. Several other more recent studies have issued similarly inconsistent findings [18][19][20].…”
Section: Introductionmentioning
confidence: 95%
“…The classification of the BMI was not a determinant factor for the occurrence of changes in the values of FEV1 and PEF. However, showed that there was no significant difference between the values obtained and provided to the respiratory measures between the eutrophic and obese groups 2,8 .…”
Section: Resultsmentioning
confidence: 86%
“…Endocrine disorders in individuals with excess weight have been associated with the accumulation of adipose tissue, the latter being responsible for the production of hormones adipokines 2 . The leptin and adiponectin are two important adipokines that are influenced by the elevation of Body Mass Index (BMI) and can be changed in the presence of pulmonary disease 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation